2015
DOI: 10.1016/j.eururo.2014.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Observational Evidence for Risk of Fatal and Nonfatal Cardiovascular Disease Following Androgen Deprivation Therapy for Prostate Cancer: A Meta-analysis

Abstract: We investigated all the available data from observational studies on hormonal treatment for prostate cancer and its possible cardiovascular adverse effects. We found consistent evidence that this treatment may increase the risk of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
150
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 234 publications
(158 citation statements)
references
References 52 publications
3
150
0
5
Order By: Relevance
“…However, even though LDL particles fuel the atherosclerotic disease process and it is well known that changes in LDL levels upon statin treatment can exert relatively rapid effects on CVD end points,27 the ADT‐associated LDL increase is modest (<10%),3 and it is doubtful whether the combined metabolic changes associated with testosterone deficiency can provide a comprehensive explanation for the acutely increased CVD risk associated with ADT initiation. Interestingly, recent observational studies and a meta‐analysis of randomized controlled trials suggested that non–testosterone‐mediated effects of GnRH agonists may be important for the increased risk of atherosclerotic CVD 4, 5. Bosco et al, using registry data, found that GnRH agonist‐based ADT was associated with a higher risk of CVD than surgical orchiectomy 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, even though LDL particles fuel the atherosclerotic disease process and it is well known that changes in LDL levels upon statin treatment can exert relatively rapid effects on CVD end points,27 the ADT‐associated LDL increase is modest (<10%),3 and it is doubtful whether the combined metabolic changes associated with testosterone deficiency can provide a comprehensive explanation for the acutely increased CVD risk associated with ADT initiation. Interestingly, recent observational studies and a meta‐analysis of randomized controlled trials suggested that non–testosterone‐mediated effects of GnRH agonists may be important for the increased risk of atherosclerotic CVD 4, 5. Bosco et al, using registry data, found that GnRH agonist‐based ADT was associated with a higher risk of CVD than surgical orchiectomy 5.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent observational studies and a meta‐analysis of randomized controlled trials suggested that non–testosterone‐mediated effects of GnRH agonists may be important for the increased risk of atherosclerotic CVD 4, 5. Bosco et al, using registry data, found that GnRH agonist‐based ADT was associated with a higher risk of CVD than surgical orchiectomy 5. Furthermore, Albertsen et al, in a meta‐analysis of trials comparing the GnRH agonists leuprolide and goserelin to the GnRH antagonist degarelix, found that agonist treatment was associated with a higher cardiovascular event rate in the subgroup of men with preexisting CVD 4…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CV risks might be increased by ADT, 5 suggesting that careful consideration of ADT modality is required before initiating treatment. However, ADT should not be withheld from men when indicated, as the priority should be optimal PC treatment.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%